Entrepreneurial competencies leading to innovative behaviour amongst academic librarians in Malaysian research universities / Haziah Sa'ari - Sa'ari, Haziah (Institute of Graduate Studies, UiTM, 2018)
This thesis reports a case study of two Malaysian public research universities (RU) academic librarians with regards to their entrepreneurial competencies leading to innovative behaviour. The primary objectives of the study are: to identify the entrepreneurial competencies leading to innovative behaviour practiced by academic librarians in two RU libraries; to explore how entrepreneurial competencies influence innovative behaviour demonstrate by academic librarians in two RU libraries; and to identify the motivational factors perceived by the academic librarians that stimulate them to demonstrate innovative performance in the context they work. Qualitative data was gathered based on a conceptual framework on entrepreneurial competencies and innovative behaviour developed, through series of focus group discussion and face-to-face interviews with 12 informants. The data shows considerable evidence from the librarians involved in this study that the Malaysian RU academic libraries are dynamic in which the practices of entrepreneurial competencies leading to innovative behaviours have taken place to a certain extent with incremental award winning innovations. The entrepreneurial competencies leading to innovative behaviours were being practiced in both cases within the parameter of their professional norms focusing on processes that contribute to the bureaucratic sluggishness inherent in the traditional structure of the academic library…